ASSOCIATIONS OF RUMINANTS IN MIOCENE ECOSYSTEMS OF EASTERN ALPINE REGION - Vislobokova I.A. (My University, 2006)
The dynamics of biodiversity of ruminants and changes in their adaptations in the Late Miocene of Austria are analyzed in connection with changes in environment and climate. At the end of the Middle Miocene through the beginning of the Late Miocene, the major reorganization of ruminant associations was recorded at the Vallesian-Turolian transition (about 8.7 Ma).
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен